Takhi Dampeng Suku Singkil di Kampung Binanga Kecamatan Rundeng Kota Subulussalam - Liza Anhar Efendi; Bustami Abubakar (Indonesian Journal of Islamic History and Culture, 2020)
Takhi Dampeng is a dance of the Singkil tribe. This dance has its own symbols and meanings as well as cultural values ​​for the community. For this reason, this article discusses the cultural values, symbols, and meanings of the Singkil tribe for the people of Binanga Village, Rundeng District, Subulussalam. The cultural values of the takhi dampeng dance to the people of Kampung Binanga has three aspects of values, namely the moral aspect, the social aspect, and the aspect of faith or divinity. The Takhi dampeng of the Singkil tribe for the people of Kampung Binanga has its own meaning and symbol. Takhi dampeng is performed in a circular manner, this process is interpreted as an effort to protect the honored guest from harm and criminals. The silat movement in takhi dampeng means the need to be ready to look after the guest of honor. The symbols contained in takhi dampeng include the appreciation of listening to poetry accompanied by a takhi dampeng musical instrument which is a symbol of the state of the soul and awakens it to build the unity of the Singkil community in solial and community life. Forming a circle in unison and swinging, lifting the legs, bending forward and other movements are symbols of the diversity of the people of Singkil which has to be maintained and open to accept diversity. Then, the typical takhi dampeng clothing is in the form of a veil, namely yellow, red, white, green and black. The yellow color is a symbol of joy, splendor used by kings. The red color is a symbol that symbolizes the courage and heroism used by commanders or knights. The white color symbolizes holiness which is used by sharia officials or religious leaders. The green color is a symbol that symbolizes fertility and justice which is used by advisors and leadership decision makers. The black color is a symbol that symbolizes the fortitude and sturdiness used by customary stakeholders.